Spatial trajectories, theories, and topoi in the study of religion and film - NG, Teng-kuan (Institutional Knowledge at Singapore Management University, 2024)
This chapter explores the correlations between religion and film studies and the geographies of religion. Using perspectives from the latter to foreground overlooked aspects of the former, I argue that investigations of the religious problematic via film are productively enriched when refocused on the question: what kind of space does religious cinema constitute? Rather than offering a single answer, I highlight the various phenomenological, ritual, and ethical spaces that cinema—comprising production, text, and reception—can construct. In the first section, I briefly trace the “spatial turns” that religion and film scholarship has taken since its inception, observing the field’s evolving geographical and global consciousness over the past four decades. Next, I consider how scholars of religion have adopted spatial sensibilities when reflecting on the nature of cinematic experience and activities. In contrast to earlier concerns with the theological and hierophanic potential of individual films, recent approaches emphasize the material and place-making aspects of religious-cinematic practices. In the third section, with reference to the work of Kim Knott, Veronica della Dora, and the Malaysian-Taiwanese filmmaker Tsai Ming-liang, I zoom in on two themes—religiosity/secularity and pilgrimage/movement—that further reveal the cinema as a site of religion-making in the contemporary world.